SLC11A2 withholds divalent metals from Salmonella in the gut epithelium - Emilia S. Norberg; Trina L. Westerman; Eddy Cruz; Summer D. Bushman; John Salogiannis; Eric P. Skaar; Johanna R. Elfenbein; Leigh A. Knodler (Proceedings of the National Academy of Sciences, 2026)
There is a constant tug-of-war for transition metals at the pathogen–host interface. Vertebrate hosts modulate the availability of metals to pathogens in a process known as nutritional immunity, but pathogens have evolved numerous countermeasures to this host defense strategy. The bioavailability of trace metals therefore shapes the outcome of disease. In mammals, epithelial cells lining the intestine are a major site of metal absorption. Intestinal epithelial cells (IECs) are also a target for invading enteric pathogens but the contribution of epithelium-intrinsic factors toward nutritional immunity is unclear. Using Salmonella enterica serovar Typhimurium (STm) harboring genetically encoded fluorescent sensors for transition metals, we mapped the spatiotemporal nature of metal competition during enteric salmonellosis. In contrast to the metal replete lumen, a subpopulation of STm experience a temporal, cell-specific restriction of Fe 2+ and Zn 2+ (≤0.1 µM), and possibly Mn 2+ , in both IECs and cells of the lamina propria during the early stages of infection. We further studied the contribution of the broad specificity divalent metal transporter, SLC11A2, in IECs to nutritional immunity against STm. SLC11A2 was recruited to maturing Salmonella -containing vacuoles and knockout of SLC11A2 led to increased bacterial proliferation in IECs. Metal-responsive fluorescent reporters showed that vacuolar STm were less starved for Fe 2+ , and possibly Mn 2+ , but not Zn 2+ or Mg 2+ in the absence of SLC11A2 . STm counters SLC11A2-mediated growth restriction in IECs via the Mn 2+ /Fe 2+ transporter, MntH, and iron-binding siderophores. We conclude that SLC11A2-mediated sequestration of a subset of metals is an IEC innate defense mechanism against STm.